Monitoring of PD Behavior - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
Partial discharge (PD) measurement is accepted worldwide as a technique to evaluate the insulation integrity of high-voltage equipment. PD monitoring is a crucial task that shows an effective way to increase the operational reliability of high-voltage equipment. The aim of PD measurement can be divided into off-line and on-line PD measurement. Off-line PD measurement is performed with the high-voltage equipment isolated from the power system. In contrast, on-line PD measurement is conducted when the high-voltage equipment is normally operating. The application of PD monitoring can be applied for the existing high-voltage equipment and the new equipment supporting smart grid technology. For application on-line PD measurement, the following issues need to be considered: importance of the equipment, potential repair time, potential cost of the damage, and so on.
Keywords: Line (geometry); High Voltage; Electrical equipment; Power grid; High voltage insulation and dielectric phenomena